A PSO based optimal repeater insertion technique for Carbon Nanotube interconnects - P, Uma Sathyakam; Raj, Shubham; Mallick, Partha S. (International Journal of Reconfigurable and Embedded Systems (IJRES), 2021)
Optimal repeater insertion is important in VLSI interconnects to reduce their propagation delay and power dissipation. We propose a particle swarm optimization (PSO) based optimal repeater number for different lengths of carbon nanotube (CNT) interconnects at 22nm and 14nm technology nodes. First, numerical equations for optimal repeaters are modelled. Secondly, a PSO based algorithm is developed and various input parameters are enlisted to train the PSO. Optimal number of repeaters and the propagation delay for CNT interconnects for lengths ranging from 500 to 2000Âµm are found out. Results are compared for both the methods and it is found that they are within 2% deviation. This means that PSO is an effective method to find optimum repeaters in VLSI interconnects. Though earlier works show similar findings, we have used CNTFET based inverters as drivers of CNT interconnects for the first time. Also, for two values of repeater size, i.e., h = 50 and 75, we have carried out the analysis.